A SURVEY OF A SUBMARINE VOLCANIC RIDGE NORTH OF SAN BENEDICTO ISLAND - Bondarenko V.I.; Rashidov V.A. (My University, 1996)
The structure of a submarine ridge north of San Benedicto Island (Revilla Gigedo Islands) is described on the basis of a survey that was carried out in 1984 by the R/V Vulkanolog.